The personality trait self-directedness predicts the amygdala’s reaction to appetizing cues in fMRI - Grimm, Oliver; Vollstädt-Klein, Sabine (Appetite, 2012)
Personality and neural response to food cues in various mesolimbic brain structures have been linked to eating disorders. We investigated the question of whether personality traits in healthy individuals correlate with the brain activation induced on confrontation with appetizing visual stimuli. Personality was assessed in 27 normal-weight participants (14 women, mean age=26.0, SD=3.3 years) with the Temperament and Character Inventory (TCI). After an overnight fast, participants viewed blocks of pictures, half containing appetizing food and the other half showing scrambled pictures as control. After each block, participants rated their appetite. Brain activation was measured using a 3T MR scanner. Food compared to control stimuli elicited a significantly higher appetite rating, as well as strong activation in the ventral and dorsal visual stream, the fusiform gyrus and consecutive limbic centres such as the parahippocampal gyrus, the amygdala, the thalamus, the insula, the ventral striatum and the orbitofrontal cortex. In a region-of-interest analysis, the TCI trait self-directedness was negatively correlated with mean blood oxygenation level dependent (BOLD) signal change in the right amygdala (r=-.43, p=.025). Ultimately, amygdala reactivity might provide a risk factor for the development of eating disorders.